Highly efficient separation of benzene + cyclohexane mixtures by extraction combined extractive distillation using imidazolium-based dicationic ionic liquids - Wanxiang Zhang; Wuji Zhao; Shuhang Ren; Yucui Hou; Weize Wu (Green Chemical Engineering, 2023)
Benzene (BEN) and cyclohexane (CYH), which have very close boiling points and a binary azeotrope, are the most difficult binary components in the separation of aromatic and non-aromatic hydrocarbons. This study further explored the separation mechanism and industrial application prospects of BEN ​+ ​CYH mixtures separated by a dicationic ionic liquid (DIL) [C5(MIM)2][NTf2]2 based on experimental research. The calculation results of the Conductor-like Screening model Segment Activity Coefficient (COSMO-SAC) model show that selectivity and solvent capacity of the DIL are significantly improved. The effects of different anions and cations on the microstructure distribution and diffusion behavior of BEN ​+ ​CYH system were investigated by quantum chemistry (QC) calculations and molecular dynamics (MD) simulations. The results indicate that the anion [NTf2]− has low polarity, uniform charge distribution, and a dual role of hydrogen bonding and π-π bonding, and the cation [C5(MIM)2]2+ has stronger interaction with BEN and higher selectivity than conventional cations. The liquid-liquid extraction and extractive distillation (LLE-ED) process using an optimized 65 mol/mol DIL ​+ ​35 mol/mol H2O mixed solution as the extractant was proposed, which solved the problem of low product purity in the LLE process and high energy consumption in the ED process. Under the best operating conditions, the purity of CYH product was 99.9%, the purity of BEN product was 99.6%, the recovery rate of BEN reached 99.9%, and the recovery rate of DIL reached 99.9%. The heat-integrated LLE-ED process reduced total annual cost by 21.6%, and reduced CO2 emissions by 48.0%, which has broad industrial application prospects.